2018
DOI: 10.20849/ijsn.v3i3.523
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lifestyle Modification Intervention on Health Status of Coronary Artery Disease Patients: Randomized Control Trial

Abstract: Background: Coronary artery disease is a major cause of morbidity and mortality throughout the world. Modification of life style can be achieved by patients' education to improve their health status. Aim: To evaluate effect of lifestyle modification intervention on health status of coronary artery disease patients. Design: Randomized control trial used to achieve the aim of this study. Setting: The current study conducted at the coronary care unit and cardiology out-patient clinics of Benha University Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…An important possible explanation for the improvement in the adherence intention to a healthy lifestyle in the present study is the significant improvement in the level of knowledge regarding prostate cancer after the application of the educational program. This is congruent with the findings of many studies (Mahmoud, and Elderiny, 2018;Klusmann, and Notthoff, 2018) that showed a positive correlation between knowledge and adherence intention to a healthy lifestyle. Improved knowledge level associated with illness and treatments has been revealed to enhance adherence intention to a healthy lifestyle (Alikari et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…An important possible explanation for the improvement in the adherence intention to a healthy lifestyle in the present study is the significant improvement in the level of knowledge regarding prostate cancer after the application of the educational program. This is congruent with the findings of many studies (Mahmoud, and Elderiny, 2018;Klusmann, and Notthoff, 2018) that showed a positive correlation between knowledge and adherence intention to a healthy lifestyle. Improved knowledge level associated with illness and treatments has been revealed to enhance adherence intention to a healthy lifestyle (Alikari et al, 2019).…”
Section: Discussionsupporting
confidence: 92%